Impact of climate change on the stock market performance of plantation firms in Malaysia - Lim, Pui Yee (2019)
El Niño is one of the well-known climate events that affect Malaysia, which has been coming back with a stronger magnitude in the recent climate cycle. It leads to high cost for plantation companies as their level of production decreases as well as cost increases to adapt to climate change. As a consequence, it ultimately affects the share price of the plantation companies. To understand the real situation, this study investigated the impact of climate change, particularly El Nino impacts on the price of share of plantation companies. The aim of the study is to find out the market risk premium and extra cost of equity for the adaption to climate change of plantation firms in Malaysia. Based on the time series data from 2009 to 2018, this study conducted the market risk and return analysis on Malaysia plantation firms, in the El Nino and non El Nino period. The 10years time series allows the research to factor in two El Nino cycles, happen in year 2009-2010, and 2015-2016. The market risk of stock was evaluated by Beta analysis, and the return and risk premium has been compared, in both period. Empirical findings discovered the impact the climate does not effectively reflected in the cost of equity in all the firms. There are firms with higher return during El Nino time, but without higher premium. The findings could assist plantation firm investor in exploring opportunities in arbitraging, and the management of plantation firms could consider the climate related index as one of the cost measurement method for equity in the near future.